A atuação do pedagogo em espaços não escolares: uma nova visão de educação - COSTA, Claudia Feio da (2023)
This work addresses as a research theme the performance of the Pedagogue in non-school spaces. Starting from our experience in the Pedagogy course at Ufpa, offered through Parfor – National Plan for Teacher Training, Abaetetuba Campus, we experienced, during graduation, through speeches by teachers and subjects offered, that the training of the Pedagogue was focused on acting only as teachers in school spaces as priority workplaces: Early Childhood Education, Elementary School I and in pedagogical disciplines, in addition to pedagogical management and coordination. We start from the assumption that the educational process is broad and is not restricted to the school environment. Based on this assumption, the present work aims to present reflections around the different and possible fields of action of the professional trained in the Pedagogy course, beyond the school environment. As a methodology, the study uses the Literature Review approach regarding the theme. As a result, we highlight the broadening of the vision regarding training, constitution of professional knowledge and the performance of the Pedagogue beyond the school environments, taking into account that educational knowledge goes beyond the knowledge that was previously restricted to public and private school institutions, but that this same knowledge can and should occupy other institutional spaces, public and private, where educational processes take place.